The impact of weight shifts on inflation: Evidence for the euro area HICP - Thomas A. Knetsch; Patrick Schwind; Sebastian Weinand (Deutsche Bundesbank, 2022)
The shifts in household consumption caused by the coronavirus pandemic affect inflation measurement in the euro area via the updating of product weights. We propose a decomposition of the inflation rate, measured by the annual percentage change of the Harmonised Index of Consumer Prices (HICP), into the aggregate price change, keeping weights constant at the previous year's level, and a weighting component. We discuss this decomposition against the backdrop of the HICP concept, considering the evolution of measurement rules over time and marking differences to a decomposition into pure price change and quantity components. Our empirical results show that euro area inflation was distinctly influenced by weighting effects for the first time in 2021. This can equally be observed for France and Italy, while comparable weighting effects in Germany already occurred prior to 2021, albeit rarely. For the period from 2013 onwards, we also provide results for the quantity effect in HICP inflation of these countries. The empirical evidence shows a close relationship between weighting and quantity effects. As weighting effects can be calculated directly from publicly available HICP data over its entire history and are comparable across individual euro area countries, we argue that this decomposition is relevant in terms of providing timely information, especially for analysts and policy-makers.
Keywords: E31; C43; 330; Inflation measurement; HICP; Updating of weights